Assessing the Influence of the Technology Acceptance Model on Social Media and eLearning Content Adoption: A Case Study of Colleges of Education in the Central and Western Zone of Ghana - Daniel Paa Korsah (Noyam Journals, 2023)
This study investigated the impact of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Perceived Reliability (PR) on the attitudes of Colleges of Education (CoE) students regarding social media and their adoption of E-learning content. As digital tools become increasingly essential in education, this research explored how students' perceptions of the utility, ease of use, and reliability of social media influence their attitudes and the adoption of eLearning content. The study also assessed gender differences in the impact of these factors on students and the implications of PR, PU, and PEOU of social media for eLearning content adoption. The research utilized a mixed-method approach that combined quantitative surveys and qualitative interviews, with 391 diverse CoE students selected through multistage sampling. The quantitative phase measured PU, PEOU, PR, and Attitude as variables, establishing their relationships through statistical analysis. In the qualitative phase, in-depth interviews provided nuanced insights into students' experiences and perceptions. The results demonstrated a positive and significant influence of social media's PU, PEOU, and PR on Attitude, as well as on eLearning content adoption. Notably, there is no significant gender-based difference in the influence of PR, PU, and PEOU on attitude, although male values slightly exceed those of females. The research also explored the implications for increasing female participation in eLearning and the potential for replication using other technology acceptance models. Educators, institutions, and developers can leverage the findings of this research to improve the design and implementation of digital tools, ultimately enhancing the educational experience for CoE students.